Induction of enantio-selective apoptosis in human leukemia HL-60 cells by (S)-erypoegin K, an isoflavone isolated from Erythrina poeppigiana. Issue 11 (1st June 2020) - Hikita, Kiyomi; Saigusa, Satomi; Takeuchi, Yuto; Matsuyama, Haruka; Nagai, Rina; Kato, Kuniki; Murata, Tomiyasu; Tanaka, Hitoshi; Wagh, Yogesh S.; Asao, Naoki; Kaneda, Norio
Graphical abstract: Highlights: Isoflavone, ( RS )-erypoegin K, was semi-synthesized as a racemic mixture. ( S )- and ( R )-optical isomers were separated by chiral column chromatography. Only ( S )-erypoegin K induced apoptosis in human leukemia HL-60 cells. The IC50 value of ( S )-erypoegin K as an anti-tumor agent was 90 nM in HL-60 cells. Abstract: Erypoegin K, an isoflavone isolated from the stem bark of Erythrina poeppigiana, has potent apoptosis-inducing effect on human leukemia HL-60 cells. Erypoegin K has a chiral carbon at the C-2′′ position of its furan ring and naturally occurs as a racemic mixture of ( S )- and ( R )-isomers. In the present study, we semi-synthesized ( RS )- erypoegin K from genistein and separated the optical isomers by HPLC using a chiral column to characterize its apoptosis-inducing activity. Apoptotic cell death was assessed by analyzing caspase-3 and caspase-9 activation, nuclear fragmentation, and genomic DNA ladder formation. ( S )-erypoegin K showed exclusive anti-proliferative and apoptosis-inducing activity, with an IC50 value of 90 nM, about 50% lower than that of its racemic mixture (175 nM). By contrast, no apoptosis-inducing activity was shown by the ( R )-isomer. In addition, methylglyoxal accumulation in the culture medium was observed only in cells treated with ( S )-erypoegin K. These results demonstrated that ( S )-erypoegin K is a unique bioactive component that has potent apoptosis-inducing activity on HL-60 cells.